PP6 Hemolytic activity of 22 plant extracts from the Colombian Caribbean - Padilla Betancourt, Francis Camila; Rodríguez Vargas, Camila; Mejía Rodriguez , Dilia; Rodriguez Palmera, Aracelys; Rodríguez Cavallo, Érika; Méndez Cuadro, Darío (Revista Productos Naturales, 2025)
The medicinal plants and herbs of the Colombian Caribbean have historically been used as primary sources for the treatment and prevention of various diseases due to their pharmacological properties. A fundamental aspect in determining their safety is the evaluation of their hemolytic activity. This is essential for protecting health, preventing risks such as hemolytic anemia and kidney damage, and complying with national and international regulatory standards. In this regard, the present study focuses on evaluating the toxicological potential of 22 plant extracts used for medicinal purposes in the municipality of San Juan de Nepomuceno.